TINGKAT KEPATUHAN MASYARAKAT TERHADAP PROTOKOL KESEHATAN DI MASA PANDEMI COVID-19 DI KELURAHAN PANGKAJENE KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Devi Novitasari; Muhammad Ikbal; Andi Astinah Adnan (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
This study aims to determine the level of public compliance with health protocols during the Covid-19 pandemic in Pangkajene Village, Maritengngae District, Sidenreng Rappang Regency and the factors that affect the level of community compliance with health protocols during the Covid-19 pandemic in Pangkajene Village, Maritengngae District, Sidenreng Rappang Regency. The population in this study is the total population of 1,753 people. The number of samples was taken by means of a random sample using Yount's formula, resulting in 88 samples. Data collection techniques used are observation, interviews, questionnaires and literature study. The collected data is then used quantitative analysis techniques with frequency tables and SPSS 16. The results showed that the level of community compliance with health protocols during the Covid-19 pandemic in Pangkajene Village, Maritengngae District, Sidenreng Rappang Regency was categorized as good in terms of numbers. 65.33%. The indicator that has the highest value is the Completeness of Health protocols in Marittenggae District (Environment). Factors that affect the level of community compliance with health protocols during the Covid-19 pandemic in Pangkajene Village, Maritengngae District, Sidenreng Rappang Regency, namely the Gender Factor is categorized as good with a value 70.2%. The Age Group factor was categorized as good with a value of 64.2%. The marital status factor is categorized as unfavorable with a value of 58%. Education factor is categorized as good value 67.2%